The Students Perceptions Of Using Open Learning as a Learning Management System In Hybrid Class - Anshary, Putri Elmira Fadyatulina; Rachman, Dzul; Khatimah, Khusnul (Borneo Educational Journal (Borju), 2024)
This research describes students' impressions of utilizing Open Learning as a Learning Management System (LMS) in hybrid classes and their issues. This case study was qualitative descriptive. This research included English Education Department students at Universitas Muhammadiyah Kalimantan Timur who used Open Learning in a Hybrid Class. Results reveal that Open Learning may be used in both face-to-face and virtual learning situations. Despite their proficiency in Open Learning, students face challenges when using it as a learning management system (LMS), including internet connectivity issues and a lack of motivation during the learning process. Living in a remote area caused internet connectivity issues, and students were unmotivated to use Open Learning as learning management system